Maternal and fetal outcome in pregnancy associated with malignancy: a case series at a tertiary care centre in India - Joshi, Shivangi; Parpillewar Tadas, Moushmi (International Journal of Research in Medical Sciences, 2025)
Malignancy in pregnancy is rare presentation with an estimated incidence of 1 per 1000. Pregnancy with malignancy poses a unique challenge for treating physician because of the safety concerns for the unborn child. The aim of the study was describing the maternal and infant outcomes of malignancy in pregnancy and to describe the various treatment options according to tumour type and gestational age. A prospective observational study was done at tertiary care centre for 6 months from December 2020 to June 2021. A case series of pregnancy associated malignancy were observed and followed up till postpartum period. Three cases were of ovarian tumors with good maternal and fetal outcomes as they were in early stages of the disease. Fourth case was of metastatic lung carcinoma with adverse maternal outcome due to advanced malignancy. The conclusion was that a multidisciplinary approach of obstetrician, pathologist, radiologist, oncologist, onco-surgeon, neonatologist is necessary in managing these cases. The treatment strategy should be discussed and structured on an individual basis. A combined approach of surgery and chemotherapy is advocated depending on the stage of the disease and gestation. Neonatal outcomes like prematurity, low birth weight are anticipated and good overall maternal and fetal outcome can be achieved.